2017
DOI: 10.1007/s10008-017-3802-1
|View full text |Cite
|
Sign up to set email alerts
|

Niobium: a promising Pd co-electrocatalyst for ethanol electrooxidation reactions

Abstract: This work reports the sol-gel synthesis and characterization of Pd x Nb y /C binary electrocatalysts applied to ethanol electrooxidation reactions (EORs). Catalysts were prepared using different Pd/Nb mass ratios (1:0; 1:1; 1:3; 3:1; 0:1) and were supported on Vulcan XC-72 carbon (20 wt%). The materials were characterized by transmission electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction, inductively coupled plasma mass spectrometry, and X-ray photoelectron spectroscopy. The EOR catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 40 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Souza et al. reported that materials containing Nb have also received special attention due to their use in heterogeneous catalysis [32] . Studies have shown that the use of Nb increases the catalytic activity, selectivity and chemical stability of conventional catalysts [32] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Souza et al. reported that materials containing Nb have also received special attention due to their use in heterogeneous catalysis [32] . Studies have shown that the use of Nb increases the catalytic activity, selectivity and chemical stability of conventional catalysts [32] .…”
Section: Resultsmentioning
confidence: 99%
“…Souza et al reported that materials containing Nb have also received special attention due to their use in heterogeneous catalysis. [32] Studies have shown that the use of Nb increases the catalytic activity, selectivity and chemical stability of conventional catalysts. [32] Souza et al have also reported that Nb is a possible cocatalyst due to the forbidden energy in the 3.1 to 4 eV band, which is ideal for the catalysis of organic compounds.…”
Section: Voltammetric Behavior Of Favipiravirmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis methods of nanomaterials are numerous, however, most of them involve a complicated series of steps: they are expensive and unfriendly to the environment, namely: chemical methods, [1][2][3][4] incipient wetness impregnation, 5 sol-gel, 6 co-precipitation, 7 hydrothermal, 8,9 electrospinning-carbonization process, 10 physical vapor deposition (PVD), 11 galvanic replacement 12 etc. Notwithstanding, electrodeposition leads the user to finer control of the experimental set ups because it displays the opposite of what we mentioned initially and allows the formation of nanoparticles, NPs, in one single step without any additives and chemical reactants, especially when the so-called deep eutectic solvents, DES, 13 are used as the electrolytic bath.…”
mentioning
confidence: 99%